2013
DOI: 10.1177/0093854813503543
|View full text |Cite
|
Sign up to set email alerts
|

Which Criminogenic Need Changes Are Most Important in Promoting Desistance From Crime and Substance Use?

Abstract: Andrews and Bonta identified the following criminogenic needs as important to reducing offending: substance use, antisocial cognition, antisocial associates, family and marital relations, employment, and leisure and recreational activities. This study examines dynamic criminogenic need changes across a 12-month period and identifies which need changes are the best predictors of criminal offending and illicit drug use among a sample of drug-involved probationers who participated in an intervention (N = 251). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
139
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 90 publications
0
139
2
Order By: Relevance
“…However, they are inconsistent with Wooditch et al's (2014) study, which found a decrease in substance use with prosocial changes in certain criminogenic needs. It should be noted that Prendergast et al (2013) did not examine adherence to the RNR model as a predictor of substance use, and Wooditch et al (2014) solely examined the need principle. This study expanded on the empirical research regarding treatment outcome and examined whether the RNR model, specifically the general responsivity principle, is associated with a substance-use outcome.…”
Section: Discussioncontrasting
confidence: 77%
“…However, they are inconsistent with Wooditch et al's (2014) study, which found a decrease in substance use with prosocial changes in certain criminogenic needs. It should be noted that Prendergast et al (2013) did not examine adherence to the RNR model as a predictor of substance use, and Wooditch et al (2014) solely examined the need principle. This study expanded on the empirical research regarding treatment outcome and examined whether the RNR model, specifically the general responsivity principle, is associated with a substance-use outcome.…”
Section: Discussioncontrasting
confidence: 77%
“…An additional study of adult drug-involved probationers did, however, examine which criminogenic need changes resulted in decreased substance use and reduced offending (Wooditch, Tang, & Taxman, 2014). Unlike prior studies discussed above, this study did not use a single standardized risk/needs assessment like the LSI-R but rather a few separate measures (such as the Criminal Thinking Scale) as well as self-report/life tables for certain risk factors.…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
“…Unlike prior studies discussed above, this study did not use a single standardized risk/needs assessment like the LSI-R but rather a few separate measures (such as the Criminal Thinking Scale) as well as self-report/life tables for certain risk factors. Wooditch, Tang, and Taxman (2014) included six of the eight prominent criminogenic needs espoused by the RNR model: antisocial attitudes, antisocial peers, family/marital relationships, work/school, leisure activities, and substance use. Probationers who evidenced decreases in risk in familial criminal networks, income, and alcohol use had reduced subsequent self-reported offending, while only changes in leisure/ recreational activities were associated with changes in substance use (Wooditch et al, 2014).…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the variables most associated with desistance, at least three are developmental (age, marriage, and work/ education; Devers, 2011). Further, work and education have been noted to be promising for intervention to promote desistance (Varghese, Fitzgerald, Chronister, Cummings, & Forrest, 2013;Wooditch, Tang, & Taxman, 2014).…”
Section: Examples Of Developmental Approach Across the Lifespan Solutmentioning
confidence: 99%